Comparison of Fine Needle Aspiration Cytology in Thyroid Lesions using The Bethesda System for Reporting Thyroid Cytopathology with Ultrasonography using Thyroid Imaging Reporting and Data System - Regmi, Sudeep; Tiwari, Archana; Sharma, Rupesh (Journal of Lumbini Medical College, 2018)
Introduction: Thyroid nodule is a common presentation. The estimated prevalence of thyroid nodules is 4-7% by clinical examination and 50-60% on ultrasonographic (USG) evaluation. Most are benign without any symptoms or cosmetic concerns. Only around 5% are found to be malignant. Methods: This prospective study evaluated a total of 54 patients with thyroid lesions presenting to Otorhinolaryngology, Surgery and Internal Medicine out-patient departments of a tertiary hospital for a period of nine months. The thyroid lesions were categorized into different categories using Thyroid Imaging Reporting and Data System (TIRADS) by USG and The Bethesda System for Reporting Thyroid Cytopathology (TBSRTC) by fine needle aspiration (FNA). The agreement between TIRADS and TBSRTC was evaluated using Cohen's kappa statistics. Results: By FNA, 68.5% were benign lesions whereas 7.4% were malignant. Follicular Neoplasm (FN) or Suspicious for FN and Suspicious for Malignancy category comprised 5.6% each. 1.9% of the lesions showed Atypia of Unknown Significance (AUS). 11.1% of the lesions were non-diagnostic or unsatisfactory for evaluation. Overall agreement between the cases by USG and FNA using the TIRADS and TBSRTC respectively was 77.77%. There was a substantial agreement between the diagnosis made by these systems, kappa (κ)= .633 (95% CI, 0.41 to 0.85, p<0.05). Conclusion: This study observed a substantial agreement between the diagnosis made by TIRADS on USG and TBSRTC on FNA. Our study advocates the stratification of thyroid lesions according to TIRADS so that only suspicious lesions undergo FNA. DOI: https://doi.org/10.22502/jlmc.v6i2.274